Radio over Fiber (RoF): A comparison of low-cost systems - Almeida, Márcio (2013)
In order to assess the potential of low-cost radio-over-fiber (RoF) solutions, in this paper we make a comparison of three full-duplex RoF systems. These systems are low-cost solutions that use remote modulation, with a single centralized light source used at the central station to generate a downlink wavelength that is reused at the remote location for upstream transmission. By avoiding the need for an additional light source at each remote location the cost of the solution is significantly reduced. The three systems evaluated in this paper differ by the type of optical modulation used for downlink and uplink. The first is an IM-IM system using intensity-modulation (IM) for the downlink and uplink direction. The second scheme, PM-IM, differs from the first by using phase-modulation (PM) for downlink. Finally, the third system, PM-PM, uses phase modulation for downlink and uplink.